2019
DOI: 10.1108/qrfm-06-2018-0078
|View full text |Cite
|
Sign up to set email alerts
|

Omani SME perceptions towards Islamic financing systems

Abstract: Purpose This paper aims to investigate small and medium enterprises’ (SMEs) owner–managers’ awareness, willingness and perceptions concerning Islamic financing instruments as an alternative sourcing decision in SMEs’ businesses. Design/methodology/approach The research employed mixed methods to gather data. A questionnaire survey was conducted via face-to-face interviews with 385 SME owner–managers operating in Muscat, Oman’s capital city, along with face-to-face discussion on Islamic finance with 86 SME own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
3
15
0
1
Order By: Relevance
“…These results support Abduh and Idrisov (2014), Muhamad et al, (2016), Albaity and Rahman (2019), Kaakeh et al (2019), andSabirzyanov's (2016) findings. Awareness also significantly affect intention to use Islamic banks, supporting Balushi et al (2019) who previously investigated the awareness of SME owners in Oman to use Islamic banks instruments. In addition, this result also supports Kaakeh et al (2018), Rammal and Zurbrugg (2007), Obeid and Kaabachi (2016).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These results support Abduh and Idrisov (2014), Muhamad et al, (2016), Albaity and Rahman (2019), Kaakeh et al (2019), andSabirzyanov's (2016) findings. Awareness also significantly affect intention to use Islamic banks, supporting Balushi et al (2019) who previously investigated the awareness of SME owners in Oman to use Islamic banks instruments. In addition, this result also supports Kaakeh et al (2018), Rammal and Zurbrugg (2007), Obeid and Kaabachi (2016).…”
Section: Discussionsupporting
confidence: 74%
“…Previous research has found that the number of Muslims using Islamic banks is limited due to a lack of awareness about Islamic banks' products itself (Islam and Rahman, 2017). Balushi et al, (2019) found that public awareness becomes one of the factors that make SME owners in Oman intent to use Islamic banks' products and services. It is also found from other studies that awareness toward Islamic banking has a significant effect on intentions to use Islamic banks' services (Kaakeh et al, 2018;Rammal and Zurbrugg, 2007;Obeid and Kaabachi, 2016).…”
Section: Awareness and Attitude Toward Islamic Bankmentioning
confidence: 99%
“…So the way is that pesantren education managers must also develop their gait (Muid, 2017). Which not only serves the process of learning religious knowledge in Islamic boarding schools but is also committed and highly dedicated to disseminating Islamic religious education to millennial generations who are not united as santri students in Islamic boarding schools (Al Balushi et al, 2019). They are ordinary students who study at school, but the rest can also adapt to a religion-based curriculum delivered in a virtual way managed by the government or religious education institutions, but they can access their homes with measurable and planned programs (Conroy et al, 2013).…”
Section: Function Of Technologymentioning
confidence: 99%
“…The most recent study i.e. Al Balushi et al (2019) investigated small and medium enterprises’ (SMEs) owner-managers’ perceptions concerning Islamic financing instruments as an alternative sourcing decision in SMEs’ businesses. However, it did not examine the factors that determine the selection criteria in detail.…”
Section: Literature Reviewmentioning
confidence: 99%